Terrestrial Water Storage Changes of Qinghai Lake on the Tibetan Plateau From Joint Inversion of GNSS and InSAR Data - Hai Zhu; Kejie Chen; Mingjia Li; Shunqiang Hu; Guoqing Zhang; Xingxing Kuang; Wenfeng Cui; Shengpeng Zhang; Junguo Liu (Water Resources Research)
Abstract Although geodetic techniques like Gravity Recovery and Climate Experiment have been widely applied to investigate terrestrial water storage (TWS) variations at regional or basin scales on the Tibetan Plateau (TP) caused by global warming, their coarse spatial has limited the study of individual lakes. In this study, we overcome this limitation by jointly using Global Navigation Satellite System (GNSS) and Interferometric Synthetic Aperture Radar (InSAR) data to generate a high‐precision, high‐resolution surface deformation field, enabling the quantitative assessment of TWS changes for Qinghai Lake, from January 2016 to December 2022. By leveraging Independent Component Analysis to extract surface deformation induced by lake hydrological loads, we find that the deformation caused by Qinghai Lake's hydrological changes is spatially limited to within approximately 25 km of the lake and is largely overshadowed by regional background loads of the TP. The region surrounding Qinghai Lake exhibited an overall trend of initial subsidence (from January 2016 to August 2019, −2.89 to −0.30 mm/yr) followed by uplift (from September 2019 to December 2022, 2.20 to 4.89 mm/yr), primarily driven by variations in precipitation patterns. Notably, we found that lake water volume increase accounts for up to 86% of the total TWS changes in Qinghai Lake, underscoring the relatively marginal role of groundwater compared to previous assessments in Inner TP where groundwater accounted for 34% of TWS changes. This study demonstrates the effectiveness of integrating GNSS and InSAR data to overcome spatial resolution limitations, providing detailed insights into the hydrological dynamics of individual lakes like Qinghai Lake, and contributes to a more comprehensive understanding of TP's hydrological changes under the influence of climate change.